1996
DOI: 10.1111/j.0022-3646.1996.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

QUANTITATIVE METHOD FOR DETERMINING A REPRESENTATIVE ALGAL SAMPLE COUNT1

Abstract: A method for determining a representative count of a sample dependent on number of species is presented for application to various algal communities. Constant species curves are calculated as efficiency = (number of individuals–number of species)/number of individuals and diagrammed on a plot of efficiency versus number of individuals counted. Efficiency is defined as the probability that a new species encountered is minimal. That is, as the ratio of number of species to number of individuals approaches 1, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 5 publications
0
46
1
6
Order By: Relevance
“…Counting efficiency followed Pappas and Stoermer (1996). Abundant and dominant species selection followed Lobo and Leighton (1986) and diatom densities (valves/cm 2 ) were based on Batarbee (1986).…”
Section: Methodsmentioning
confidence: 99%
“…Counting efficiency followed Pappas and Stoermer (1996). Abundant and dominant species selection followed Lobo and Leighton (1986) and diatom densities (valves/cm 2 ) were based on Batarbee (1986).…”
Section: Methodsmentioning
confidence: 99%
“…And, if the latter, how should effort be split between spatial and temporal replicates from the same water body? Pappas & Stoermer (1996) showed that the number of taxa recorded increases as effort spent per sample increases. But does this extra information on biodiversity actually contribute to our knowledge about ecological status at a site?…”
Section: Dealing With Variabilitymentioning
confidence: 99%
“…Os indivíduos foram identificados e contados em microscópio óptico Olympus CX31, até que um mínimo de 600 valvas fosse registrado, conforme recomendações de Kobayasi & Mayama (1982), com uma eficiência de contagem de 90% (Pappas & Stormer 1996). As espécies abundantes e dominantes foram determinadas de acordo com o critério de Lobo & Leighton (1986), que consideram abundantes aquelas espécies cujas densidades superam a densidade média da amostra e dominantes aquelas espécies cujas densidades superam 50% da densidade total da amostra.…”
Section: Methodsunclassified